2014
DOI: 10.3389/fnhum.2014.00698
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Dysfunctions of Impulse Control – A Systematic Review in Borderline Personality Disorder and Attention-Deficit/Hyperactivity Disorder

Abstract: Disorders such as borderline personality disorder (BPD) or attention-deficit/hyperactivity disorder (ADHD) are characterized by impulsive behaviors. Impulsivity as used in clinical terms is very broadly defined and entails different categories including personality traits as well as different cognitive functions such as emotion regulation or interference resolution and impulse control. Impulse control as an executive function, however, is neither cognitively nor neurobehaviorally a unitary function. Recent fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 144 publications
(339 reference statements)
5
93
0
3
Order By: Relevance
“…Impulsivity is a dimension that is shared by bipolarity and ADHD (Perugi et al, 2013c;Sebastian et al, 2014), but in clinical practice the differential diagnosis between the mood instability that is typical of ADHD and that of a comorbid mood disorder, especially if "soft", as in the case of cyclothymia, or if complicated by substance abuse, is a really hard one to formulate (Asherson, 2005;Perugi et al, 2013c). In any case, specific studies are almost entirely lacking.…”
Section: "Comorbidity" and Its Complicationsmentioning
confidence: 97%
“…Impulsivity is a dimension that is shared by bipolarity and ADHD (Perugi et al, 2013c;Sebastian et al, 2014), but in clinical practice the differential diagnosis between the mood instability that is typical of ADHD and that of a comorbid mood disorder, especially if "soft", as in the case of cyclothymia, or if complicated by substance abuse, is a really hard one to formulate (Asherson, 2005;Perugi et al, 2013c). In any case, specific studies are almost entirely lacking.…”
Section: "Comorbidity" and Its Complicationsmentioning
confidence: 97%
“…Impulsivity consists of different components including personality traits (eg, tendency to act on the spur of the moment), deficits in executive functions (eg, attention, interference inhibition, information sampling, decision making, delay of gratification), and behavioral inhibition (Sebastian et al, 2013(Sebastian et al, , 2014. Aggressive behavior frequently displayed by patients with BPD (Latalova and Prasko, 2010) and ADHD (Connor et al, 2010) is usually of two different kinds: reactive (or impulsive) aggression and instrumental aggression.…”
Section: Introductionmentioning
confidence: 99%
“…On a neural level, these symptoms have been associated with abnormalities in fronto-limbic networks, including the anterior cingulate cortex (ACC) (Mancke et al, in press;Sacchetti and Lefler, 2014;Sebastian et al, 2014). In previous research, altered ACC structure and function have been demonstrated in BPD (Rusch et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Participants reporting a lifetime diagnosis of a borderline personality disorder were also excluded, as this disorder is known to be associated with impairments in inhibitory control and decision making. 30 We obtained oral and written informed consent from all participants before including them in the study. The study was conducted in accordance with the Declaration of Helsinki and was approved by the local ethics committee of the Medical School of the University of Heidelberg.…”
Section: Participantsmentioning
confidence: 99%